Enhancement of spectroscopic and luminescence properties of Er3+ doped tellurite glasses by adding P2O5 for lasing materials - Jlassi, I.; Fares, H. [UNESP]; Elhouichet, H. (Elsevier, 2018)
Er3+-doped phosphor-tellurite glasses has been synthesized by conventional melting method. Results of differential scanning calorimetry (DSC) measurements indicate a good thermal stability of tellurite glasses. The DSC measurements show an improvement of thermal stability of glass hosts after adding P2O5. The structures of glasses were investigated by X-ray diffraction (XRD) and Raman spectroscopy to understand their dependence of structure on composition. Absorption spectrum from near infrared to visible was obtained and the Judd–Ofelt (J-O) intensity parameters (Ω2, Ω4, and Ω6) were determined. Spontaneous emission probabilities of some relevant transitions, branching ratio, and radiative lifetimes of several excited states of Er3+ have been predicted using intensity J-O parameters. Up-conversion luminescence characteristics, under 977 nm excitation wavelength, have been investigated at room and low temperature in these glasses. Intense green and red emissions from Er3+ centered at 534 nm, 548 nm and 660 nm, corresponding to the transitions 2H11/2→4I15/2, 4S3/2→4I15/2 and 4F9/2→4I15/2, respectively, were simultaneously observed. The quadratic dependence of the up-conversion emission on the excitation power indicates that two-photon steps are involved for the three visible emission bands. The PL lifetimes is found to decrease in the temperature range 77–300 K. Using the Mc-Cumber method, emission cross-section (σe), Absorption cross-section (σa), and gain cross-section (G(λ)) for the 4I13/2→4I15/2 transition, were calculated. By analyzing obtained data based to all advantages after adding P2O5, the tellurite glasses can be used as potential host material for developing optical amplifiers applied for 1.53 µm band broad and high-gain erbium-doped fiber amplifiers (EDFA).
Keywords: Rare earth ions; Reabsorption phenomenon; Tellurite glasses; Temperature effect; Up-conversion emission, PL lifetime